Adult dyslexic readers benefit less from visual input during audiovisual speech processing: fMRI evidence. (August 2018) - Francisco, Ana A.; Takashima, Atsuko; McQueen, James M.; van den Bunt, Mark; Jesse, Alexandra; Groen, Margriet A.
Abstract: The aim of the present fMRI study was to investigate whether typical and dyslexic adult readers differed in the neural correlates of audiovisual speech processing. We tested for Blood Oxygen-Level Dependent (BOLD) activity differences between these two groups in a 1-back task, as they processed written (word, illegal consonant strings) and spoken (auditory, visual and audiovisual) stimuli. When processing written stimuli, dyslexic readers showed reduced activity in the supramarginal gyrus, a region suggested to play an important role in phonological processing, but only when they processed strings of consonants, not when they read words. During the speech perception tasks, dyslexic readers were only slower than typical readers in their behavioral responses in the visual speech condition. Additionally, dyslexic readers presented reduced neural activation in the auditory, the visual, and the audiovisual speech conditions. The groups also differed in terms of superadditivity, with dyslexic readers showing decreased neural activation in the regions of interest. An additional analysis focusing on vision-related processing during the audiovisual condition showed diminished activation for the dyslexic readers in a fusiform gyrus cluster. Our results thus suggest that there are differences in audiovisual speech processing between dyslexic and normal readers. These differences might be explained by difficulties in processing the unisensory components of audiovisual speech, more specifically, dyslexic readers may benefit less from visual information during audiovisual speech processing than typical readers. Given that visual speech processing supports the development of phonological skills fundamental in reading, differences in processing of visual speech could contribute to differences in reading ability between typical and dyslexic readers. Highlights: Dyslexic readers were slower in their responses to the visual speech condition. Dyslexic readers showed reduced neural activation in all speech conditions. In terms of superadditivity, dyslexic readers also showed decreased activation. Dyslexic readers presented diminished activation in a fusiform gyrus cluster. Differences in audiovisual processing may be explained by unisensory differences.